(untitled) - Iniewski, Krzysztof (Boca Raton, 2008)
The 22 chapters in this collection explore design options, RF building blocks, chip architectures, circuit implementations, and fabrication processes for the next generation of wireless communication systems. The contributors, who are a mix of academic and industry researchers, propose novel circuit solutions for multiple-input multiple-output radio transceivers, an algorithmic design methodology for simultaneous noise and input impedance matching in low-noise amplifiers, and a digital RF processor. Other topics include body area networks for health monitoring, the MB-OFDM ultra wide band system, receivers for short-distance wireless links, fractional PLLs for multiband synthesis, distributed effects in RF CMOS chips, and membrane-based MEMS systems.
Keywords: Wireless communication systems,Metal oxide semiconductors, Complementary,Radio circuits,Vô tuyến điện; Equipment and supplies,Design and construction,Design and construction